2016
DOI: 10.1038/srep22571
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mechanism of action of auranofin against multi-drug resistant bacterial pathogens

Abstract: Traditional methods employed to discover new antibiotics are both a time-consuming and financially-taxing venture. This has led researchers to mine existing libraries of clinical molecules in order to repurpose old drugs for new applications (as antimicrobials). Such an effort led to the discovery of auranofin, a drug initially approved as an anti-rheumatic agent, which also possesses potent antibacterial activity in a clinically achievable range. The present study demonstrates auranofin’s antibacterial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 58 publications
12
136
0
Order By: Relevance
“…However, a recent crystallographic study conducted by Parsonage et al (2016) revealed that auranofin most likely does not bind to the cysteine residues in TrxR of E. histolytica . Another study, conducted by our research group, also demonstrated that TrxR is not the primary target of auranofin in bacteria (Thangamani et al, 2016a). We demonstrated that auranofin inhibits multiple biosynthetic pathways including DNA, protein and cell wall synthesis in bacteria (Thangamani et al, 2016a).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…However, a recent crystallographic study conducted by Parsonage et al (2016) revealed that auranofin most likely does not bind to the cysteine residues in TrxR of E. histolytica . Another study, conducted by our research group, also demonstrated that TrxR is not the primary target of auranofin in bacteria (Thangamani et al, 2016a). We demonstrated that auranofin inhibits multiple biosynthetic pathways including DNA, protein and cell wall synthesis in bacteria (Thangamani et al, 2016a).…”
Section: Discussionmentioning
confidence: 70%
“…Another study, conducted by our research group, also demonstrated that TrxR is not the primary target of auranofin in bacteria (Thangamani et al, 2016a). We demonstrated that auranofin inhibits multiple biosynthetic pathways including DNA, protein and cell wall synthesis in bacteria (Thangamani et al, 2016a). However, the exact molecular target of auranofin, in bacteria, still remains unclear.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , and Enterobacter cloacae were obtained from the American Type Culture Collection (Manassas, VA, USA). Escherichia coli OP50, E. coli 1411 and E. coli ΔAcrAB were described before 41, 42 . The human colorectal cell line (HRT-18) was obtained from the American Type Culture Collection (Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%